Simultaneous stimulated Raman gain and loss detection (SRGAL) - Heuke, Sandro (Opt Express, 2020)
The fidelity of stimulated Raman scattering (SRS) microscopy images is impaired by artifacts such as thermal lensing, cross-phase modulation and multi-photon absorption. These artifacts affect differently the stimulated Raman loss (SRL) and stimulated Raman gain (SRG) channels making SRL and SRG image comparisons attractive to identify and correct SRS image artifacts. To provide answer to the question: "Can I trust my SRS images?", we designed a novel, but straightforward SRS scheme that enables the dectection of the stimulated Raman gain and loss (SRGAL) simultaneously at the same pixel level. As an advantage over the conventional SRS imaging scheme, SRGAL doubles the SRS signal by acquiring both SRL as well as SRG and allows for the identification of SRS artifacts and their reduction via a balanced summation of the SRL and SRG images.